Quality Of Services in Flamboyan Flats on Resident Satisfaction - Puspasari, Aprilia; Styaningrum, Etik Dwi; Supriatin, Supriatin; Mustomi, Dede (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research aims to analyze the quality of services provided by Rusunawa Flamboyan. Responding to residents' complaints, conducting evaluations, and developing service quality standards are the issues discussed in this research. This research is quantitative and uses the Servqual method with 50 respondents and 50 questionnaires which have gone through validity testing, reliability testing, and hypothesis testing. In testing using the Servqual method on residents of Rusunawa Flamboyan, it was found that they had an average perception of 3.72 regarding the five dimensions of Servqual, while the expected value was 3.36. Thus, there is a difference of 0.36 which is positive, indicating that the service in the five Servqual dimensions has met the residents' expectations.